A Comparison of Unmet Needs for Dental and Medical Care - Kevin C. Heslin, PhD; William E. Cunningham, MD, MPH; Marvin Marcus, DDS, MPH; Ian Coulter, PhD; (2000)
Oral health conditions associated with HIV disease are frequently more severe than those of the general population, making access to both dental and medical care important. Using the domains specified in the Behavioral Model of Health Services Use, this paper examines the correlates of unmet needs for dental and medical care in a nationally representative sample ofpatients with HIV